The Effect of the Surface Roughness of Porcelain on the Adhesion of Oral Streptococcus mutans - Al-Marzouk, Maan Ibrahim; Al-Azzawi, Haitham J (Seer Publishing LLC, 2009)
Aim: Dental plaque has a harmful influence on periodontal tissue. When a porcelain restoration is fabricated and refinishing of the glazed surface is inevitable, the increase in surface roughness facilitates the adhesion of plaque and its components. The aim of this in vitro study was to evaluate the effect of surface roughness of glazed or polished porcelain on the adhesion of oral Streptococcus mutans.